One-year outcomes of selective laser trabeculoplasty for open-angle glaucoma in Indian eyes - Anuj Sharma; Arpita Nayak; Shamika Ghaisas; K Vidya (Indian Journal of Ophthalmology)
Purpose: To assess the effectiveness of selective laser trabeculoplasty (SLT) in Indian eyes with open-angle glaucoma (OAG). Settings and Design: Single-center, prospective, interventional study. Methods: Patients undergoing SLT from January 2014 to June 2018 for OAG were included in the study. Treatment-naive naive as well as patients on antiglaucoma medications (AGM) with suboptimal intraocular pressure (IOP) control were included. The main outcome measure was the percentage reduction in IOP. Complete success was defined as IOP reduction > 20% from baseline after 12 months or reduction in the number of AGM. Qualified success was defined as > 20% IOP reduction at 12 months with AGM. Secondary outcomes were occurrence of adverse events and factors predicting treatment outcomes. Results: A total of 104 eyes of 62 Indian patients underwent SLT for OAG. Eighty-three (79.81%) eyes were treatment-naïve, and 21 (20.19%) eyes were on AGM. The median (IQR) baseline IOP was 20 (16–26) mmHg. At 12 months, the median IOP was 16 (4–19) mmHg, the median decrease in IOP was 4 (0–6.5) mmHg, and the percentage reduction in IOP was 17.42% (0%–30.76%). Maximum IOP reduction was noted at 12 months. Overall, success was achieved in 48 (46.15%) patients. Five eyes (4.8%) experienced minor SLT-related complications. Age, gender, prior use of AGM, type of OAG, and higher baseline IOP were not found to be predictive factors for treatment outcome. Conclusion: SLT was found to be a relatively safe and effective procedure in Indian eyes with OAG.